Two years follow up study on an ad hoc telephone interpreters' emotional regulation program - Bruno, Luana; Iborra Cuéllar, Alejandro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The following study shows the main qualitative results obtained by means of a two follow up study with a group of telephone interpreters who previously participated in an ad hoc emotional regulation program designed according to their specific needs. The study aimed to evaluate the impact of the intervention program in the long term. The results demonstrated the positive effect of the program on the interpreters’ lives and on their emotional management. The need of verifying the effect of this kind of programs in order to totally measure their impact through the time is discussed.